Rabies Encephalitis With Myocarditis Mimicking ST-Elevation Myocardial Infarction - Park, Stacy C (Open Forum Infect Dis, 2019)
Rabies virus infection remains a significant public health threat particularly in developing countries without effective canine vaccination programs. After symptoms develop, there is no effective treatment and mortality approaches 100%. In countries such as the United States where human rabies remains rare, initial diagnosis is often delayed. In this study, we describe a case of rabies encephalitis presenting with concern for acute ST-elevation myocardial infarction (STEMI) based on electrocardiogram, laboratory, and exam findings and briefly review the known literature on cardiac involvement of rabies virus infection.